The Impact of Digitalisation of Higher Education: The Case of Latvia and Nordic-Baltic Region - Petrovica Sintija; Anohina-Naumeca Alla; Avanesova Jelena (Applied Computer Systems, 2022)
For the next seven years, the digitalisation of higher education is one of the priority tasks of Latvia. An extensive review of information sources was performed, and an online survey with the technical staff of higher education institutions was conducted to evaluate the progress made towards education digitalisation in Latvia and compare these results with the countries of the Nordic-Baltic region. The paper presents the study results and identifies issues hindering the digitalisation progress, e.g., issues with the legislation, basic digital skills, and required competences for academic staff.